Introduction - Tolan, John (De Medio Aevo, 2023)
The historiography concerning Medieval Christian Muslim-Relations over the past sixty years has been shaped by two important books: Norman Daniel’s Islam and the West (1960) and Edward Said’s Orientalism (1978). Each of these works made significant contributions to the field, but each also had serious methodological limitations. Both works assumed and reinforced a conceptual divide between an imagined Christian West and Muslim East. Over the past several decades, some of the most interesting and important work in the field has challenged and reconceptualized this dichotomy.